Penentuan Jalur Evakuasi Pada Kawasan Rawan Bencana Tsunami - Ahmad Kurniawan; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The purpose of this study is to map evacuation routes in tsunami-prone areas. The research location is along the coast of Galesong District, Takalar Regency. Data collection techniques carried out were interviews, agency studies, literature reviews, and field observations. The method used in determining the level of threat of a tsunami disaster at the location of the study was spatial analysis, descriptive analysis, and weighting analysis based on tsunami height and exposed population index wich is substituted into the threat level matrix. While to determine the mapping of tsunami evacuation routes is the least cost path method. The method determines the most optimal evacuation path (time and distance) from tsunami-prone areas to the location of temporary evacuation. Determination of the optimal route is based on surface costs or cost weighted distance by considering land use and slope in the study area. The results of the research obtained based on the threat level matrix are all villages in the study area belong in the high threat class for the tsunami disaster. Evacuation shelter building that meet the criteria are spread throughout the Galesong District area. The number of temporary evacuation sites is 34 units. The results of the analysis of at least track costs are 66 of the most optimal total evacuation routes to the location of evacuation shelter building.